REINTERPRETASI KONSEP PUNISHMENT BAGI PESERTA DIDIK DALAM HADIS PENDIDIKAN ṢALAT - Prastio Prastio (MGMP PAI Jawa Barat, 2022)
Rasulullah was a gentle and loving person. Meanwhile in one of the hadiths there is a